Magnetic Solid-Phase Extraction Based on C18 Nanoparticles for the Determination of Pesticides in Aquaculture Water Samples - Margarita Kapsi; Vasileios Sakkas; Vasiliki Boti; Triantafyllos Albanis (Molecules)
In this study, C18-functionalized magnetic silica nanoparticles (Fe3O4@SiO2@C18) were used as adsorbents for the magnetic solid-phase extraction (MSPE) of organic contaminants commonly applied to aquaculture water (organic booster biocides, herbicides, and insecticides) followed by Gas Chromatography coupled to Mass Spectrometry (GC–MS). The extraction conditions and efficiency of the nanoparticles for the determination of ten pesticides (atrazine, ethoxyquine, chlorothalonil, chlorpyriphos methyl, methyl parathion, chlorpyriphos, resmethrin, λ-cyhalothrin, permethrin, and irgarol) were thoroughly investigated. Several experimental parameters affecting the extraction efficiency such as the amount of sorbent, extraction time, and elution time were optimized by employing experimental designs as response surface methodology. Validation experiments showed that the average recoveries of target analytes were in the range of 60% to 99%. The optimized method exhibited good linearity (R2 > 0.9901) and satisfactory precision (Relative Standard deviations, RSDs < 15%). The method detection limits ranged between 1.9 ng L−1 and 62 ng L−1. Finally, the MSPE method was successfully applied to aquaculture water samples collected from the Thesprotia region (N.W. Greece), Thermaikos Gulf (N. Greece) and Butrint (S.W. Albania).